CRITICAL SET OF EDGE MAGIC TOTAL LABELING OF EXPANDING CYCLE GRAPH * - Chairul Imron; Suhud Wahyudi (Limits: Journal of Mathematics and Its Applications, 2010)
This paper discusses about graph labeling. We will nd edge magic total labeling of cycle and expanding cycle graph. In the nal, we investigate the critical set of edge magic total labeling on cycle and expanding cycle graph.